Specialized interfaces of Smc5/6 control hinge stability and DNA association - Aaron Alt (Nature Portfolio, 2017)
Structural Maintenance of Chromosomes (SMC) complexes maintain genome integrity by regulating the segregation of chromosomes. Here, Altet al. describe the structure of the heterodimeric Smc5/6-hinge from fission yeast and define functional features critical for Smc5/6’s cellular function.